«Volte: e le cose già non sono più»: Carmelo Bene per Dino Campana - Piazza, Laura (Mimesis Journal, 2017)
The essay deals with Carmelo Bene’s interpretation of Dino Campana’s poetry. With the Canti Orfici concert, in March 1982, Bene gave a fundamental contribution to the reception of Campana, which he thought to be the greatest Italian poet after Dante. The encounter with Campana will exert a singular influence on the Bene’s theory of deconstruction of word and scene. Campana’s poetry well suits with the revolution of the signifier perpetrated by Bene not only because of the sound’s quality and the visual intensity, but also because of the sound movement and the short-circuit generated by the persistent use of the anaphora and by considerable number of variants. In the deliberate choice to confuse the biographical contours of the author together with the articulated Canti’s philological history, Campana interpreted by Bene is an invention created by him. Bene uses it in order to de ne his resolute path towards a “theater of becomingness”, because «the only thing that remain is what eternally passes and flees». This is a non-place theater where one can dismally attend to the show of poetry in its making, where the orphic poet-actor Bene finally goes back to being the interpreter of the voice of gods.